A bright chemiluminescence conjugated polymer–mesoporous silica nanoprobe for imaging of colonic tumors in vivo. Issue 10 (19th April 2022) - Li, Yukun; Zhu, Beibei; Han, Wanying; Tang, Wei; Duan, Xinrui
Abstract : A chemiluminescence (CL) conjugated polymer–mesoporous silica nanoprobe with significant improvement of CL quantum yield obtained from direct oxidation of a conjugated polymer and its application for in vivo imaging of colonic tumors. Abstract : Hypochlorite acid (ClO − ) is one of the major reactive oxygen species (ROS) in colon cancer, providing an effective target for colonic tumor in vivo imaging. For detection of ClO − and tumor imaging, poly[(9, 9-di(2-ethylhexyl)-9 H -fluorene-2, 7-vinylene)- co -(1-methoxy-4-(2-ethylhexyloxy)-2, 5-phenylenevinylene)] (PFV- co -MEHPV, namely CP1) was encapsulated in mesoporous silica nanoparticles (MSNs) that were pre-modified with polyphenylenevinylene (PPV) via in situ polymerization to construct bright PPV@MSN-CP1 nanoparticles. The synthesized nanoparticles were size-stable and not cytotoxic as confirmed by FE-TEM, FE-SEM, and MTT assay. Hypochlorite oxidizes the vinylidene bond of CP1 through π 2 –π 2 cycloaddition to form PPV-dioxetane intermediates to generate photons. The CL quantum yield of PPV@MSN-CP1 was 16.7 times higher than that of Pluronic F-127 wrapped CP1. CL nanoparticles PPV@MSN-CP1 have good selectivity for hypochlorite detection among biological oxidants (mainly ROS). The linear range and the LOD of PPV@MSN@CP1 for ClO − detection are 4–90 and 1.02 μM, respectively. Subsequently, we further coated PPV@MSN@CP1 with folic acid for tumor targeting by phospholipid wrapping. PPV@MSN-CP1@FA was successfully applied for in vivo imaging of endogenously produced ClO − of tumor tissue in living animals.